Penggunaan Pusat Kerajinan sebagai Sumber Belajar: Pembelajaran Kertakes Berbasis Kontekstual - Amir Amir (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
Using of handicraft centre as resources of art and handicraft learning can be seen as one of the application of the competency based education curriculum. The handicraft learning can be effective if the learn in the real context, i.e. handicraft centre. Using of handicraft centre as learning resources can facilitate teachers and students in learning, motivate students make relation between knowledge and ordinary application, and give students ways of problem solving.